Effect of immersion and inoculation in ovo of Lactobacillus spp. in embryonated chicken eggs in the prevention of Salmonella enteritidis after hatch - Yamawaki, R. A.; Milbradt, E. L.; Coppola, M. P.; Rodrigues, J. C Z; Andreatti Filho, R. L.; Padovani, C. R. [UNESP]; Okamoto, A. S. (My University, 2013)
The protection level against Salmonella Enteritidis was evaluated in chickens after in ovo treatment with different species of Lactobacillus spp. inoculated into the air cell or by immersion in broth culture. Two hundred forty embryonated eggs were distributed into 8 groups, corresponding to treatments with Lactobacillus acidophilus, Lactobacillus fermentum, Lactobacillus salivarius, and control. On d 18 of incubation, 4 groups were inoculated with 0.1 mL of inoculum in the air cell and 4 groups were immersed for 3 min in culture of each treatment. Two days after hatching, 0.5 mL of Salmonella Enteritidis culture was inoculated by the intraesophageal route. On d 5 of life, the chicks were euthanized and the ceca were processed to obtain Salmonella Enteritidis counts. There was no decrease in Salmonella Enteritidis colonization of chick ceca, regardless of treatment or route of administration. Lactobacillus spp. samples used in the treatment showed no probiotic potential in chicks when inoculated in ovo, in relation to Salmonella Enteritidis inhibition in poultry ceca. © 2013 Poultry Science Association Inc.
Keywords: Embryonated egg; In ovo; Lactobacillus; Salmonella; probiotic agent; animal; animal salmonellosis; bird disease; chick embryo; chicken; controlled clinical trial; controlled study; microbiology; oocyte; physiology; randomized controlled trial; Salmonella enteritidis; Animals; Chick Embryo; Chickens; Ovum; Poultry Diseases; Probiotics; Salmonella Infections, Animal